Production of Wet Organic Waste Ecoenzymes as an Alternative Solution for Environmental Conservation Supporting Sustainable Development Goals (SDGs): A Techno-Economic and Bibliometric Analysis - Afridha Sesrita; Helmia Tasti Adri; Irman Suherman; R. Rasmitadila; Muhammad Zainal Fanani (ASEAN Journal for Science and Engineering in Materials, 2025)
This study investigates the techno-economic feasibility of producing ecoenzymes from wet organic waste, supported by a bibliometric analysis of relevant global research trends. Spanning a 20-year projection, the study evaluated the production costs, potential profitability, and market pricing of ecoenzymes as an environmentally friendly product. Results indicated that even small-scale, home-based production was economically viable, requiring a minimal daily capital investment of $0.27 (or approximately $80,625 annually). With a selling price of IDR 200,000 per kg, the projected annual revenue was IDR 400,000,000. Notably, the return on investment was achieved within the first three years. The bibliometric analysis highlighted a growing global focus on sustainable waste-to-product conversion. The novelty of this study lied in its application of techno-economic modeling to a previously underexplored product, ecoenzymes from wet organic waste. The findings contribute to multiple Sustainable Development Goals (SDGs), especially SDG 11 (Sustainable Cities), SDG 12 (Responsible Consumption and Production), and SDG 13 (Climate Action).